ASME 2009 InterPACK Conference, Volume 2 2009
DOI: 10.1115/interpack2009-89325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transient Heating on Two-Phase Flow Response in Microchannel Heat Exchangers

Abstract: Two-phase microfluidic heat sinks promise high heat flux cooling at reduced pumping power compared to pumped liquid microchannel heat sinks. However, flow instabilities caused by bubble nucleation and expansion severely reduce heat transfer performance of two-phase microfluidic heat sinks. This study probes the governing physics of bubble nucleation and expansion by comparing the effects of pulsed heating to steady-state heating in a single microchannel. Pulsed heating at 8 Hz causes an increase in the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The interest in a pulsed heating strategy has continuously increased in recent years for thermal management applications. Miler et al [48] experimentally characterized transient phenomena in a water-fed single microchannel heat exchanger during pulsed heating (frequency f s = 8 Hz and pulse duration t s = 31 ms). The authors observed that low-frequency/highduration pulsed heating leads to an increase in the average hotspot temperature.…”
Section: Active Control Of Flow Instabilitymentioning
confidence: 99%
“…The interest in a pulsed heating strategy has continuously increased in recent years for thermal management applications. Miler et al [48] experimentally characterized transient phenomena in a water-fed single microchannel heat exchanger during pulsed heating (frequency f s = 8 Hz and pulse duration t s = 31 ms). The authors observed that low-frequency/highduration pulsed heating leads to an increase in the average hotspot temperature.…”
Section: Active Control Of Flow Instabilitymentioning
confidence: 99%
“…Regarding the experimental research under nonuniform heat flux, the wall temperature cannot be simply calculated based on the one-dimensional heat conduction equation, so the heat transfer coefficient cannot be obtained. Therefore, most of the previous studies that are relevant to the present work [11,13,14] directly presented the measured wall temperature as the indicator of the cooling performance of heat sinks at given conditions. The wall temperature, however, reflects the conjugated effects of both fluid convection and wall conduction on the cooling performance.…”
Section: The Role Of Diamond Wall Conductionmentioning
confidence: 99%
“…Placing the hotspot near the outlet can effectively reduce the CHF. In addition, some experimental efforts have explored the flow boiling instabilities [11], flow maldistribution [12,13], transient behavior of heat transfer [14,15] under nonuniform microchannel heating. These studies provide a basis for understanding the physical mechanism of heat transfer in microchannels under nonuniform heating conditions.…”
Section: Efficiency 1 Introductionmentioning
confidence: 99%
“…Maldistribution was caused by a local increase in two-phase pressure drop due to boiling, which diverted single-phase liquid to other locations; this effect was most pronounced for a hot spot at the inlet. Transient non-uniform heating situations have also been investigated [19,21].…”
Section: Introductionmentioning
confidence: 99%